ZoologyCon 2024 - Book of Abstracts - Luis Ovidiu Popa; Costică Adam; Maxim-Jean Bâlcu; Andreea Maria Brezeanu; Ioana Cristina Constantinescu; Larisa Bianca Farcaș; Ana-Maria Krapal; Rozalia Magda Motoc; Alexandra Popa; Oana Paula Popa; Florentina Purdescu; Melania Stan; et al. (Travaux du Muséum National d’Histoire Naturelle “Grigore Antipa”)
The book contains the abstracts and program of the international zoological congress ZOOLOGYCON 2024, organized by the Grigore Antipa Museum and held in Bucharest, Romania from 6th to 9th November 2024.